1996
DOI: 10.1073/pnas.93.5.2186
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from conserved regions of paramyxovirus fusion (F) proteins are potent inhibitors of viral fusion.

Abstract: The synthetic peptides DP-107 and DP-178 (T-20), derived from separate domains within the human immunodeficiency virus type 1 (HIV-1) transmembrane (TM) protein, gp4l, are stable and potent inhibitors of HIV-1 infection and fusion. Using a computer searching strategy (computerized antiviral searching technology, C.A.S.T.) based on the predicted secondary structure of DP-107 and DP-178 (T-20), we have identified conserved heptad repeat domains analogous to the DP-107 and DP-178 regions of HIV-1 gp4l within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
294
2
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(313 citation statements)
references
References 38 publications
10
294
2
7
Order By: Relevance
“…However, at a concentration of 10 g/ml or 2.8 M, the GP64 peptide inhibits slightly Ͻ50% of Sf9-RBC fusion and Sf9 cell-to-cell fusion. This concentration is several orders of magnitude greater than the 50% syncytial inhibition value of 100 pM reported for DP178 inhibition of HIV-mediated cell-to-cell fusion (Wild et al, 1994b) but may be closer to values reported for paramyxovirus fusion, which range from 0.015 to 2.1 M (Lambert et al, 1996;Yao and Compans, 1996).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…However, at a concentration of 10 g/ml or 2.8 M, the GP64 peptide inhibits slightly Ͻ50% of Sf9-RBC fusion and Sf9 cell-to-cell fusion. This concentration is several orders of magnitude greater than the 50% syncytial inhibition value of 100 pM reported for DP178 inhibition of HIV-mediated cell-to-cell fusion (Wild et al, 1994b) but may be closer to values reported for paramyxovirus fusion, which range from 0.015 to 2.1 M (Lambert et al, 1996;Yao and Compans, 1996).…”
Section: Discussionsupporting
confidence: 58%
“…Hydrophobic 4-3 heptad repeat motifs are clearly important for pH-independent viral protein-mediated fusion (Chen et al, 1995;Reitter et al, 1995;Lambert et al, 1996;Young et al, 1997). For HIV gp41 peptide inhibition, it has been predicted that peptides would exert inhibitory effects during the conformational change to the fusion-active conformation (Wiessenhorn et al, 1997).…”
Section: The Heptad Repeat-dependent Stage Of Membrane Fusionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the majority of research into the fusion function of RSV F has been focused on regions within the F 1 subunit, in particular, the HRA and HRB coiled coil (23)(24)(25). While these studies have provided deeper insight into formation and antiviral targeting of the terminal 6HB fusion core (26), the roles of residues and domains within the F 2 subunit remain relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%